"Ufunda de ufe" : the story of a village psychologist in a rural, South African school setting - Theunissen, Maureen Ezelle (Rhodes University, Faculty of Humanities, Department of Psychology, 2002)
In 2001, participatory research, incorporating various participatory rural appraisal techniques, was conducted in five, rural, primary schools in the Eastern Cape, South Africa. The participatory research was aimed at identifying and addressing schools' needs in terms of lifeskills education in a changing South Africa and educational environment. This whole process has been written up as a case study and further analysed in an attempt to describe the emerging role of the psychologist, working in participation with educators, in this kind of setting. Going beyond description, the researcher reflects upon the function and nature of the role of the psychologist within the developmental participatory process. In doing so, the article addresses the need for participatory research results to be further analysed in generating theory, particularly within Psychology. The article highlights some of the strengths of qualitative research, and the primacy of the personal in that endeavour.
Keywords: Participant observation; Rural children -- Education -- South Africa; Life skills -- Study and teaching -- South Africa